Pharmaco Therapeutic Profiles of Chandraprabhavati An Ayurvedic Herbo Mineral Formulation - Sushama B Bhuvad, Dr (International Journal of Pharmaceutical & Biological Archive, 2013)
Pharmaco Therapeutic Profiles of Chandraprabhavati An Ayurvedic Herbo Mineral Formulation